An incomplete markets explanation of the UIP puzzle - Katrin Rabitsch (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
A large literature attributes failure of uncovered interest rate parity (UIP) to the existence of a timevarying risk premium. This paper presents a mechanism in a simple two-country two-good endowment economy with incomplete markets that generates sizeable deviations from UIP. In a parameterization where international wealth effects are important, liquidity constraints on an internationally traded bond and agents' strong resulting precautionary motives successfully generates a time-varying risk premium: countries that have accumulated large outstanding external positions have, being closer to the constraints, stronger precautionary motives and their asset carries a risk premium.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: F31; F41; G12; G15; 330; Uncovered Interest Rate Parity; Incomplete Markets Precautionary Savings; Time-Varying Risk Premium